2014
DOI: 10.1002/srin.201300262
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Study of Nitrogen Removal from the Vacuum Tank Degasser

Abstract: Low nitrogen content in liquid steel is required for most of the steelmaking companies, where vacuum degassing of liquid steel is usually carried out to remove nitrogen as well as other impurity elements during ladle treatment. This paper presents an integrated computational fluid dynamics (CFD) model for simulating the nitrogen removal in an industrial vacuum tank degasser (VTD). In the CFD model, oxygen and sulfur are considered as surface-active elements decreasing the denitrogenation rate at the gas-steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The CFD model has been tested with a set of examples and it has proven to be capable of capturing the main features of multiphase flows in the VTDs and of predicting final [H] or [N] content by comparisons with some industrial data. [21,22,34] In this paper, the convergence criteria of all simulations are 10 À3 for mass, momentum, and turbulence equations and 10 À6 for species equations. A base case is firstly simulated to demonstrate the integrated model.…”
Section: Cfd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFD model has been tested with a set of examples and it has proven to be capable of capturing the main features of multiphase flows in the VTDs and of predicting final [H] or [N] content by comparisons with some industrial data. [21,22,34] In this paper, the convergence criteria of all simulations are 10 À3 for mass, momentum, and turbulence equations and 10 À6 for species equations. A base case is firstly simulated to demonstrate the integrated model.…”
Section: Cfd Resultsmentioning
confidence: 99%
“…[14] Some related experiments on a laboratory scale have been conducted using a constant amount of surfaceactive elements and the results showed that the denitrogenation can be described as a second-order reaction. [8,15,16] The effect of some alloying elements on nitrogen removal behavior has also been examined [17][18][19][20][22][23][24] and the results revealed that the elements such as titanium (Ti), zirconium (Zr), vanadium (V), manganese (Mn), and chromium (Cr), which have stronger affinity with nitrogen than iron, would enhance the nitrogen dissociation rate (the reaction rate for the reverse reaction of nitrogen desorption), whereas the elements such as aluminum (Al), silicon (Si), boron (B), (copper) Cu, wolfram (W), and tin (Sn) having stronger repulsive force against nitrogen would retard the dissociation rate.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, vacuum results are influenced not only by technological parameters of processing, but also by a large number of technological and organizational factors [2][3][4][5][10][11][12][13][14][15][16][17][18][19][20]. Therefore, despite a large number of studies on the effects of hydrogen and nitrogen in vacuuming [10][11][12][13][14][15][16][17][18][19][20], the study of the results of steel degassing in specific production conditions allows us to obtain new patterns and improve the production technology.…”
Section: The Overview Of the Problemmentioning
confidence: 99%
“…Based on previous work on the E-E model, the simultaneous reaction model (SRM) coded by these researchers was added to investigate the metal-slag reactions. In contrast, Yu et al [118][119][120][121][122] mainly focused on investigating the dehydrogenation and denitrogenation behaviors in an industrial vacuum tank degasser with different operating conditions. A recent work by Li et al [39] used the PBM to calculate the bubble size distribution affected by the coalescence and breakage in the plume.…”
Section: E-e Modelmentioning
confidence: 99%